CHANGING THE PHYSICAL AND CHEMICAL PROPERTIES IN THE APPLICATION CONTAINING ADJUVANTS - Baio, F. H. R.; Gabriel, R. R. F.; Camolese, H. da S. (Revista Brasileira de Engenharia de Biossistemas, 2015)
This work aimed to evaluate the changes produced by twelve adjuvants in some physicochemical properties of the pesticides application, over the wetting area of ​​soybean leaves and the change in droplet size. The evaluations were conducted under controlled environmental conditions in the laboratory. Two flat fan nozzle models were used to evaluate the variation of the droplet size: SF standard fan nozzle; and TT pre-chamber. The variation analysis of the drop spreading over the leaf surface was performed using ImageJ software. The surface tension and viscosity of the mixtures were measured by simple laboratory methods such as the drop mass measurement and Stokes method, respectively. All adjuvants reduced the surface tension of the spray mixture. The adjuvant Break-Thru silicone based gave a reduction in surface tension of 3.6 times compared to distilled water and also showed the highest solution spreading over the leaf surface by 13.5 times. However, it also had the highest drop evaporation rate. Except adjuvant Break-Tru, all adjuvants showed similar statistically to control evaporation up to 30 minutes after application. The adjuvant Gota Max provided the largest increment over the mixture viscosity and the adjuvant Hygrogem the greatest reduction over viscosity compared to water. The use of adjuvant to decrease the droplet size and increases the percentage of droplets greater than 100 micron when the tip is SF type. When using the tip TT, the addition of an adjuvant to the spray solution had no impact on the droplet size variation or the variation of the Span index, but increased the percentage of droplets smaller than 100 micron by using the Break-Thru adjuvant. The use of adjuvant Gota Max provided greater relative amplitude when using the tip SF.